Selective Biosensors and Their Applications - Ahmad A. Suleiman (Research Highlights in Science and Technology Vol. 7, 2023)
There has been a rather phenomenal growth in the field of biosensors with potential applications in a variety of disciplines, including clinical, environmental, food, security, and military areas. In this manuscript, the analytical characteristics of a selective variety of biosensors developed previously in our laboratory will be described.